Long-term decline of marine viruses associated with warming and oligotrophication at a NW Mediterranean coastal site - Lopez Alforja, Xabier (2025)
Viruses play key roles in controlling microbial abundance and community composition, nutrient cycling, and productivity in marine systems. Rising ocean temperatures, alongside increasing oligotrophy, are expected to alter the availability of inorganic nutrients and oxygen—key environmental factors that shape microbial community structure and virus-host interactions. While many studies have investigated viral abundances and community structure across spatial gradients, less is known about their long-term temporal variations, which is particularly relevant in the current context of global change. To address this gap, we analyzed two decades of surface water data from the Blanes Bay Microbial Observatory, located at the North Western Mediterranean, to describe how biotic and abiotic variables influence temporal dynamics of viral abundances and community composition. Statistical tools for time series, including GAMMs, anomaly analysis, and neural networks allowed us to demonstrate that viral abundance follow strong seasonality and a clear decrease starting midway (ca. 2011) through the sampled period (2005-2022). Fingerprint analysis evidenced that viral community composition was significantly influenced by seasonality and some environmental and biotic, with strong differences in viral communities between summer and winter months. Our analyses revealed that over the last 18 years, the abundance of most microbial groups, including viruses and their potential hosts, have declined, coinciding with an increase in seawater temperature and transparency, as well as a notable decrease in nutrient concentrations and phytoplankton biomass. We identified the ongoing shift towards more oligotrophic conditions as a potential driver of the observed decline in viral abundance, particularly in the last decade.